The Promotion of Dark Septate Endophytes on the Performance and Active Ingredients Accumulation of Dendranthema morifolium Under Cd Stress - Meiling Wu; Gen Li; Simiao Wang; Ziteng Wang; Longfei Li; Li Han (Agronomy)
Dark septate endophytes (DSE) may facilitate plant growth and stress tolerance in stressful ecosystems. However, little is known about the response of medicinal plants to DSE, especially under heavy metal stress. This study aimed to investigate how DSE affects the growth of Dendranthema morifolium in medicinal plants under cadmium (Cd) stress. In this investigation, the sterile and non-sterile inoculations were carried out to evaluate the effect of three DSE strains on D. morifolium stressed with Cd. For the root, DSE15 sterile or non-sterile inoculation resulted in enhanced root biomass, root volume, the Cd content of roots, and the indoleacetic acid (IAA) levels in D. morifolium under Cd stress. DSE7 non-sterile inoculation significantly enhanced the Cd content of roots at 1 and 5 mg Cd/kg soil. Regarding impact stems and leaves, under sterile conditions, DSE7 and DSE15 effectively regulated the shoot biomass, plant height, chlorophyll level, and superoxide dismutase (SOD) content. Under sterile conditions, DSE15 positively influenced shoot biomass and plant height, while DSE7 had no significant effect on them when subjected to Cd stress. For effects on flowers under non-sterile conditions, DSE7 and DSE15 significantly increased the flower biomass under Cd stress, while DSE7 reduced the Cd transfer coefficient of flowers at 1 and 5 mg Cd/kg soil. Importantly, at 1 mg Cd/kg soil, DSE7 and DSE15 non-sterile inoculations promoted the 1, 5-dicaffeoylquinic acid content by 18.29% and 21.70%. The interaction between DSE and soil factors revealed that DSE species had significant effects on soil organic carbon and available nitrogen in D. morifolium non-sterile soil. The DSE15 inoculation enhanced soil organic carbon content, while the inoculation of DSE7 and DSE15 reduced soil available nitrogen content under Cd stress. These results contribute to a better understanding of DSE-plant interactions in habitats contaminated by heavy metals and demonstrate the potential utility of DSE strains for cultivating medicinal plants.